Effect of dental procedures under general anesthesia on life quality and dental fears in 2-5 year-old children - Naser Kaviani; Seyed Ebrahim Jabarifar; Marjan Babadi Boroujeni (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: During the past decade, attention to oral health-related quality of life has greatly increased. This study was designed to evaluate the effect of dental treatment under general anesthesia on the quality of life and dental fears in 2‒5 year-old children. The other aim of this study was to explore the effect of dental fears on oral health-related quality of life in children.Materials and Methods: This descriptive-analytical study was carried out on sixty-five 2‒5 year-old healthy children referring to the operating room of Isfahan Faculty of Dentistry for dental treatment under general anesthesia. ECOHIS (Early Childhood Oral Health Impact Scale) and CFSS-DS (Children's Fear Survey Schedule- Dental Subscale) questionnaires were used to assess the oral health-related quality of life and dental fears. The questionnaires were completed by parents before and after the dental procedures. Paired-sample t-test and Spearman's and Pearson's tests were used for data analysis at a confidence interval of 0.95. Results: Oral health-related quality of life significantly improved after dental treatment under general anesthesia (p value < 0.05). Mean scores before and after were 42.78 and 24.56, respectively, with statistically significant differences. In addition, the mean score of dental fear decreased from 46.29 to 42.20, which was statistically significant (p value < 0.001).Conclusion: Dental treatment under general anesthesia can significantly improve oral health-related quality of life and decrease dental fears in children. Key words: Dentistry, Fear, General anesthesia, Pediatric dentistry, Quality of life